The Role of Islamic Education Curriculum Management in Enhancing Health Literacy Among Muslim Adolescents at MA Darussalam Krempyang - Niken Ristianah (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2025)
The study titled